Unilateral GPi-DBS Improves Ipsilateral and Axial Motor Symptoms in Parkinson’s Disease as Evidenced by a Brain Perfusion Single Photon Emission Computed Tomography Study - Hayashi, Yuka; Mishima, Takayasu; Fujioka, Shinsuke; Morishita, Takashi; Inoue, Tooru; Nagamachi, Shigeki; Tsuboi, Yoshio (Frontiers in Human Neuroscience, 2022)
Introduction: Deep brain stimulation (DBS) is a highly effective therapy for advanced Parkinson’s disease (PD) with the primary treatment being bilateral subthalamic nucleus deep brain stimulation (STN-DBS). While the effectiveness of STN-DBS has been well documented, detailed investigations of unilateral DBS of the globus pallidus internus (GPi) are scarce. Materials and Methods: Seventeen patients with Parkinson’s disease (PwPD) who underwent unilateral Gpi-DBS were selected. We conducted comparison analyses between scores obtained 6–42 months pre- and postoperatively using the following measurement tools: the Movement Disorder Society Unified Parkinson’s Disease Rating Scale (MDS-UPDRS) part III, the Hoehn and Yahr stage, the presence/absence of dyskinesia, Mini-Mental State Examination (MMSE), Frontal Assessment Battery (FAB), Geriatric Depression Scale (GDS), levodopa equivalent dose (LED), and cerebral blood flow tomography (99mTc-ECD SPECT). Patient backgrounds were compared between four cohorts with favorable (good responders, ≥50% improvement) and unfavorable (poor responders, <50% improvement) postoperative outcome. Results: Significant improvement was observed postoperatively in the following: total MDS-UPDRS Part III scores during the off period, contralateral scores, ipsilateral scores, and axial scores. Similarly, the Hoehn and Yahr stages during the off period, and GDS also showed significant increases. In contrast, LED, MMSE, and FAB remained unchanged while the number of patients who scored positive for dyskinesia decreased by 40%. Abnormal cerebral blood flow preoperatively seen in the cerebral cortex had normalized in the total score-based good responder cohort. In the ipsilateral score-based good responder cohort, cerebral blood flow increased in the contralateral frontal lobe including in the premotor cortex, contralateral to the DBS. Compared to the poor responders, postoperative good responders demonstrated significantly higher preoperative MMSE scores. Discussion: Unilateral GPi-DBS therapy was effective in improving contralateral, ipsilateral, and axial motor symptoms of patients with advanced PD; in particular, it was found to be especially beneficial in PwPD whose cognitive function was unimpaired; the treatment efficacy rivaled that of bilateral counterparts up till at least 6 months postoperatively. Finally, normalization of preoperative abnormalities in cerebral blood flow and increased cerebral blood flow in the contralateral frontal lobe indicated the beneficial potential of this therapy on ipsilateral motor symptoms.